2018
DOI: 10.1038/gim.2017.262
|View full text |Cite
|
Sign up to set email alerts
|

A metabolomic map of Zellweger spectrum disorders reveals novel disease biomarkers

Abstract: Untargeted metabolomics is effective in detecting mild to intermediate cases of PBD-ZSD. Surprisingly, dramatic reductions in plasma sphingomyelin are a consistent feature of the PBD-ZSD metabolome. The use of metabolomics in PBD-ZSD can provide insight into novel biomarkers of disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
41
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 38 publications
10
41
1
Order By: Relevance
“…This approach resulted in an overall diagnostic rate of 12.3% (21/170 = 12.3% [ Table 1 ]). 10 , 13 , 16 18 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach resulted in an overall diagnostic rate of 12.3% (21/170 = 12.3% [ Table 1 ]). 10 , 13 , 16 18 …”
Section: Resultsmentioning
confidence: 99%
“…We have previously described the use of untargeted metabolomics in the screening and diagnosis of a variety of inborn errors of metabolism (IEMs) 9 and the identification of novel disease biomarkers. 10 , 11 We have also demonstrated that untargeted metabolomics may be useful in the diagnosis of individuals at either end of a phenotypic spectrum, as in the case of several individuals with adenylosuccinate lyase deficiency 12 and in patients with GABA-transaminase deficiency 13 . Here, metabolomic data were not only able to suggest a clinical diagnosis but also informed the choice of targeted molecular testing for additional confirmation.…”
Section: Introductionmentioning
confidence: 95%
“…The accumulation of putrescine is associated with another inborn error of metabolism, cystinuria 40 . The concentration of hexadecanedioate is elevated in the Peroxisome Biogenesis Disorders-Zellweger Syndrome Spectrum disorders 41 . Biotinidase deficiency is an inborn error of metabolism that affects the endogenous recycling of biotin, causing neurological and cutaneous symptoms 42 .…”
Section: Maternal Factors Affecting Inborn Errors Of Metabolism (Iemsmentioning
confidence: 99%
“…Urine, plasma and CSF metabolomic assays have been employed, revealing significant findings on clinically analysed samples [58,[85][86][87][88]. These insights include new diagnostic biomarkers [87][88][89], a broader range of phenotype in adenylosuccinate lyase deficiency [90], insights around pre-analytical factors [91], primary metabolic variations from drug-related changes [92][93][94] and a better understanding of the underlying pathobiological mechanism of disease [95][96][97].…”
Section: Biomarker Discoverymentioning
confidence: 99%